The Effect of Combined Qur’anic Murottal and Dhikr Therapy on Postoperative Pain in Patients Undergoing Coronary Artery Surgery - Tri Endah Pangastuti; Eska Riyanti; Nelly Yardes; Wartonah Wartonah; Santa Manurung; Ace Sudrajat; Nadhia Elsa Silviani; Dewi Lusiani (Jurnal Persatuan Perawat Nasional Indonesia (JPPNI), 2026)
ObjectiveThis study aimed to examine the effect of a combination of Qur’anic murottal recitation and dhikr therapy on pain intensity among patients following coronary heart disease surgery.MethodsA quantitative pre-experimental study using a one-group pretest–posttest design was conducted involving 20 postoperative cardiac surgery patients selected through purposive sampling.  Data were collected from postoperative day 1 to day 5 in 2025 at a cardiac surgical ward of a referral hospital in Indonesia.  All participants continued receiving standard analgesic therapy according to clinical protocols.  To minimize pharmacological bias, the intervention was administered consistently two hours after routine analgesic administration.  The intervention consisted of listening to Surah Ar-Rahman murottal recitation for 15 minutes followed by guided dhikr for 5 minutes.  Pain intensity was measured using the Numeric Rating Scale (NRS).  Data were analyzed using descriptive statistics and the Wilcoxon Signed Rank Test with a significance level of p < 0.05.ResultsThe mean pain score significantly decreased from 4.15 ± 1.29 before the intervention to 3.00 ± 1.25 after the intervention (p = 0.001). Most respondents experienced a shift from moderate pain to mild pain following therapy.ConclusionThe combination of Qur’anic murottal and dhikr therapy is effective as a complementary nursing intervention for reducing postoperative pain in patients undergoing coronary heart disease surgery and may be integrated into clinical nursing practice alongside standard analgesic management.KeywordsComplementary therapy, coronary heart disease, dhikr, murottal, postoperative pain